Decision-making of autonomous driving based on reinforcement learning - Shi, Max Ziyi (Nanyang Technological University, 2024)
This project aims to utilize a particular machine learning technique called reinforcement learning (RL) in order to develop a particular technological aspect of autonomous vehicles (AV) called decision-making. A few commonly used RL algorithms such as PPO, SAC & TD3 will be implemented along with optimization in order to build and train RL models that will allow a self-driving car in a simulated environment to operate autonomously. The models are evaluated based on quantitative metrics that ensures safety and dynamic performance of the AV.